Tips and Techniques in Laparoscopic Surgery - Dulucq, Jean-Louis (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This comprehensive manual demonstrates basic laparoscopic techniques step-wise, with emphasis on practical details and tips. Every procedure is described in six main steps, richly illustrated with actual operative images and explicit sketches. Special emphasis is given to the right way to perform the techniques and the dangers to be avoided. Reading this book, the laparoscopic surgeon will have a practical and complete overview of the array of procedures.